Cultural Values and Preservation Efforts of the Karo Ethnic Ndikkar Dance in Lingga Village, Simpang Empat District - Ginting, Yoe Anto; Gulo, Hubari (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Ndikkar dance is a rich and valuable cultural heritage of the Karo tribe in Lingga Village, Simpang Empat District. This dance reflects deep cultural values and is an important part of the Karo ethnic identity. Social changes and the influence of modernization can threaten this dance's sustainability. This research aims to identify and analyze the cultural values of the Ndikkar dance and develop effective preservation strategies to maintain cultural continuity. The research method used is a qualitative method with an interactive model. Data collection using participant observation, interviews, and literature study to holistically understand the Ndikkar dance and its cultural context. The research results show that the Ndikkar dance contains various cultural values, including religious, social, and aesthetic values. There are various challenges, such as the changing values of the younger generation and a lack of institutional support, that could threaten the survival of this dance. Holistic conservation efforts involving community participation, strengthening cultural values in education, and collaboration between the government and the community are important keys to preserving the Ndikkar dance and Karo tribal culture as a whole.